Experiences of living with asthma – a focus group study with adolescents and parents of children with asthma. (March 2014) - Jonsson, M.; Egmar, A-C.; Hallner, E.; Kull, I.
Abstract Objective: The goal for asthma treatment is that every individual, so far as possible, shall live without symptoms and exacerbations. Patients and health care professionals sometimes have different perceptions of what is important for achieving good quality of life. This work aims to describe the experiences among adolescents as well as those of parents with young children living with asthma. Methods: Four focus group interviews were performed, two with parents of young children and two with adolescents. The data were qualitatively analyzed, using Systematic Text Condensation. Result: Three themes relevant to the participants' experiences of living with asthma were presented; strategies, frustrations and expectations. The adolescents wanted to be like their peers and developed their own strategies for self-management of asthma, which included not always taking medication as prescribed. The parents emphasized frustration regarding not being believed, lack of understanding feelings of loneliness, or anxiety. One identified expectation was that the participants wanted to be met with competence and understanding in asthma care from health care professionals. Another expectation expressed among parents was that teachers in nursery and primary schools should have more knowledge and understanding on how to care for children with asthma. Conclusion: Living with asthma leads to developing personal strategies in self-management of asthma. Moreover both parents and adolescents had expectations of being met by competent and understanding health care professionals. Developing a partnership between patients and health care professionals could be a successful way to improve the care of patients with asthma.